Evaluation of Polyethylene Glycol (PEG-6000) Induced Drought Stress Tolerant Mungbean Genotypes by using Correlation, Principal Component, Hierarchical Clustering and Multi-Trait Genotype-Ideotypes Distance Index Analysis - Islam, Mohammad Rafiqul; Hossain, Akbar; Akhter, Mst. Masuma; Alam, Mohammad Ashraful; Azam, Mohammad Golam; Hossain, Jamil; Gaber, Ahmed; Islam, Mohammad Sohidul (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
Determining a plant’s ultimate population under water stress requires seedling establishment and germination. The current study was aimed at identifying mungbean genotypes that were tolerant to drought stress. The treatments were: Factor A: polyethylene glycol 6000 (PEG-6000) inducing different levels of water potential (i.e., 0.0 (distilled water as a control), -0.7, -1, -2, and -4 bar) and Factor B: Thirty-three mungbean genotypes, collected from various national and international organizations. Each genotype’s seeds were planted in a petri dish (9 cm diameter) containing sand bed and were moistened with appropriate amounts of water potential and left to develop into seedlings of all genotypes for up to 10 days. The findings showed that when PEG-6000 concentration was raised, germination, shoot and root length, and the associated fresh and dry weights decreased significantly. Among these tested genotypes, BMX-08010-2, BMX-08009-7, BMX-01015, BARI Mung-8, BARI Mung-2, and BU Mung-2 were found to be tolerant against drought stress based on their % germination and germination indices, as well as their seedling traits. Principal component analysis, multi-trait genotype-ideotype distance index (MGIDI), two-dimensional heat map, and hierarchical clustering analysis also revealed the same genotypes to be stable and capable of withstanding water deficiency stress. In response to water stress, the genotypes BARI Mung-1, BARI Mung-3, BU Mung-4, and BMX-05001 showed poor germination indices along with relatively poor seedling characteristics. The results of the present research provide criteria for the selection of drought-tolerant mungbean genotypes in future breeding programs.